Phytochemicals Screening and Antioxidant Effectiveness of Garlic (Allium sativum) from Timor Island - Priska, Melania; Peni, Natalia; Carvallo, Ludovicus (Biosaintifika: Journal of Biology & Biology Education, 2019)
The people of Timor Island only know garlic as a kitchen spice. This research provides new knowledge of the benefits of garlic in the health sector, especially as an inhibitor of free radical that can trigger various degenerative diseases. The aims of this research were to identify secondary metabolites contained in the ethanolic extract of garlic (Allium sativum L.) from Timor Island and to determine its effectiveness in inhibiting free radicals. The method used to test secondary metabolites was phytochemical screening using color reagents. Testing the effectiveness of free radical inhibitors from garlic ethanol extract from Timor Island was carried out in 2 stages: 1.) Determination of DPPH maximum wavelength (λ) and 2.) Measurement of antioxidant activity using DPPH method. The results showed that the ethanolic extract of garlic from Timor Island contained secondary metabolites of flavonoids, phenols and terpenoids. It was also very effective in inhibiting free radicals, with the acquisition of IC50 values <50 ppm which was equal to 9.729 ppm. This research gives some information that can be used for the pharmacological ingredients, i.e. as a natural medicine that safe for the body to be consumed by the people of Timor Island. Moreover that also can impact on demand of garlic in the market. This has a very positive impact on improving the economy of garlic farmers on Timor Island.